Pengetahuan, Sikap, dan Perilaku Penggunaan Suplemen dan Obat Tradisional pada Tenaga Kesehatan di Jember selama Pandemi COVID-19 - Dhita Evi Aryani; Antonius Nugraha Widhi Pratama; Ika Norcahyanti; Sinta Rachmawati; Fransiska Maria Christianty; Ema Rachmawati; Gustia Alinda Lintarsari (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Healthcare workers play the role as the front line in treating COVID-19 patients, so they are at risk of being exposed by this virus therefor it is necessary to always maintain health and increase their immunity. One way is taking supplements or traditional medicines. The behavior of taking supplements or traditional medicines is influenced by knowledge and attitudes. The purpose of this study was to determinate the knowledge, attitudes, and behavior of using supplements and traditional medicines among healthcare workers in Jember during the COVID-19 pandemic. This research was an observational analytic study with a cross-sectional design involving 376 healthcare workers in Jember selected by convenience sampling method.The data collection instruments was questionnaires. The results showed that the majority of respondents had good knowledge (52.1%) and moderate attitudes (59.0%). Sociodemographic factors that influence knowledge are level of education and the type of healthcare worker, while the factors that influence attitudes are age, level of education, type of health worker, and working time. There is a significant relationship (p≤0.05) between knowledge and attitudes which can be concluded that knowledge influences attitudes towards the use of supplements and/or traditional medicines